1996
DOI: 10.1029/95ja02835
|View full text |Cite
|
Sign up to set email alerts
|

Auroral N2 emissions and the effect of collisional processes on N2 triplet state vibrational populations

Abstract: Previous model results have shown that the N2 triplet vibrational level populations in the aurora are strongly affected by cascade and quenching by atomic and molecular oxygen. As the aurora penetrates to lower altitudes (less than 100 km) the role of quenching by atomic oxygen becomes less important and processes involving N2 collisions begin to play a more prominent part. We are developing a model which will yield steady state vibrational level populations for both the singlet and triplet valence states of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 66 publications
4
91
1
1
Order By: Relevance
“…The rates associated to vibrational redistribution within N 2 (A 3 S u + ) with Dv = 3 are zero up to v = 17 [Morrill and Benesch, 1996;J. S. Morrill, private communication, 2009].…”
Section: Kinetic Scheme and Chemical Speciesmentioning
confidence: 99%
See 3 more Smart Citations
“…The rates associated to vibrational redistribution within N 2 (A 3 S u + ) with Dv = 3 are zero up to v = 17 [Morrill and Benesch, 1996;J. S. Morrill, private communication, 2009].…”
Section: Kinetic Scheme and Chemical Speciesmentioning
confidence: 99%
“…which rate coefficients are taken from Morrill and Benesch [1996]. The rates associated to vibrational redistribution within N 2 (A 3 S u + ) with Dv = 3 are zero up to v = 17 [Morrill and Benesch, 1996;J.…”
Section: Kinetic Scheme and Chemical Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, high-energetic auroral electrons penetrate to these altitudes causing the type B aurora (Gattinger and Vallance Jones, 1979;Gattinger et al, 1985). Benesch (1981Benesch ( , 1983, Morrill and Benesch (1996), Kirillov (2008a) have shown that vibrational populations of the triplet manifolds of molecular nitrogen are strongly affected by collision processes at the altitudes. This dependence of vibrational populations of Correspondence to: A. S. Kirillov (kirillov@pgia.ru) electronically excited N 2 on the rates of collisional processes causes a redistribution of First Positive Group (1PG) relative intensities with the increase in the density of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%